Macroporous heparin-based microcarriers allow long-term 3D culture and differentiation of neural precursor cells. (February 2020) - Newland, Ben; Ehret, Fanny; Hoppe, Franziska; Eigel, Dimitri; Pette, Dagmar; Newland, Heike; Welzel, Petra B.; Kempermann, Gerd; Werner, Carsten
Abstract: Adult neurogenesis and the neurogenic niche in the dentate gyrus are subjects of much research interest. Enhancing our knowledge of this niche process and the role played by this unique microenvironment would further our understanding of plasticity and its relevance for cognition in health and disease. The complex three-dimensional (3D) nature of the niche microenvironment is poorly recapitulated in current cell culture experimental procedures. Neural precursor cells (NPCs) are cultured either on two-dimensional (2D) surfaces, where cells quickly reach confluency and passaging is required, or as 3D neurospheres, with the limitation of poor diffusion of nutrients and thus partial differentiation of cells over time. Herein, we culture NPCs on microscale scaffolds termed microcarriers, composed of poly(ethylene glycol) and heparin, designed to more closely represent the 3D environment of the neurogenic niche. The interconnected macroporous structure of the microcarriers allows NPCs to attach to their pore walls with subsequent continuous proliferation (analyzed up to 28 days) without formation of a necrotic core. Removal of basic fibroblast growth factor and epidermal growth factor from the culture medium results in differentiation of the NPCs. Unlike 2D culture, a high percentage of neurons was achieved on the microcarriers (22% MAP2 positive cells) indicating that these 3D microscale scaffolds give a more conducive environment for neuronal differentiation. Microcarrier culture of NPCs allows long-term cell expansion and better differentiation, which provides superior culture conditions for studying/modelling the neurogenic niche.